Growth of a newly isolated oleaginous microalgal strain (Asterarcys sp. RA100) in oil produced water and its potential for biodiesel production. - Raeid M M Abed; Huda Al Battashi; Thirumahal Muthukrishnan; Hamzah Al-Bartamani; Mahmood Al-Hinai; Maryam Al-Baluchi (PLoS ONE)
The prospects of using produced water (PW), a by-product of oil extraction, as a cultivation medium to not only grow microalgae but also generate value-added by-products has not been much investigated. This study demonstrates the ability of a newly isolated microalga, Asterarcys sp. RA100, for growth in PW and biodiesel production. Although the used PW was slightly alkaline (pH < 10), nutrient deficient and high in boron content, Asterarcys sp. RA100 exhibited good growth with phosphate, and nitrate, reaching optimal growth at 1% salinity, 25°C, 150 rpm, and 4000-8000 Lux LED light intensity. To test for its scalability in a greenhouse, Asterarcys sp. RA100 exhibited areal productivity of 10.3 ± 0.5 g m-2 day-1. Lipid accumulation in Asterarcys sp. RA100 reached 27.0 ± 5.1% of dry weight when grown in PW. The resulting fatty acids methyl esters (FAME) displayed properties aligning with international biodiesel standards. The FAME profiles showed elevated contents of palmitic acid (C16:0), elaidic acid (C18:1n9t), stearic acid (C18:0) and palmitoleic acid (C16:1n7C). This study demonstrates the immense potential of Asterarcys sp. RA100 to grow in PW and to serve as valuable feedstock for biodiesel production thereby, providing an eco-friendly method to re-use PW and sustain future energy demands.